Answer:
The solution for the given polynomial
is
![x = ((-1)/(2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/h3dntfbwsagd1jvka7fjiw12q2go1acbxj.png)
Explanation:
Here, the given quadratic equation is :
![4x^2 + 4x+ 1 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/acfygg0c0snoj3dud0j7672cjszza8eoyp.png)
Now, here solving the given equation by SPLITTING THE MIDDLE TERM:
![4x^2 + 4x+ 1 = 0 = 4x^2 + 2x+ 2x + 1 = 0\\\implies 2x( 2x + 1) + 1(2x + 1) = 0\\\implies (2x +1)(2x +1) = 0\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oinaird19a5d9lgz1v7w16ek00iu5s8dun.png)
⇒ either (2x+1) = 0, or ( 2x + 1) = 0
⇒ x = -1/2 or x = -1/2
Here, in both the cases, the value of x is equal i.e x = -1/2
So, the given function has TWO IDENTICAL ROOTS.
Hence the solution for the given polynomial
is
![x = ((-1)/(2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/h3dntfbwsagd1jvka7fjiw12q2go1acbxj.png)